How business digitalization can effect the entrepreneurial growth - B Lena Nuryanti; Ajeng Putri Hanifah; Asep Indra Cahyadi (Goodwood Publishing, 2023)
Purpose: This study aims to determine the effect of business digitalization on entrepreneurial growth conditions for young entrepreneurs in the city of Bandung. Research methodology: This quantitative research uses the explanatory survey method with data collected from 31 young entrepreneurs who were members of HIPMI PT through observations, interviews, and questionnaires. The data collected were processed using the Statistical Product for Service Solution (SPSS) 24.0 for Windows. Results: The result showed that the condition of business digitalization and entrepreneurial growth at HIPMI PT in Bandung City is at a fairly good level, with the condition of respondents in implementing business digitalization improved to improve the entrepreneurial growth conditions. Limitations: This research was conducted with a small scope of research objects due to the author's limitations. Therefore, future research needs to update business digitalization and entrepreneurial growth theory. This is in addition to other dimensions that affect entrepreneurial growth but have not been proven properly in this research. Contribution: This research positively affects the condition of HIMPI PT in Bandung City related to business digitalization and entrepreneurial growth. Novelty: Factors influencing entrepreneurial growth mostly come from variables outside the study.